2020
DOI: 10.24912/provitae.v13i2.9647
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Parental Beliefs dan Self-Regulated Learning terhadap Pemahaman Bacaan Siswa SMP di Bali

Abstract: The research examined the contribution of parental beliefs and students’ self-regulated learning simultaneously toward students’ reading comprehension of junior high school in Bali. The separate examination has also been carried out namely the contribution of Balinese parental beliefs on students' reading comprehension and the contribution of students’ self-regulated learning on reading comprehension. The sample of this research consisted of 71 junior high school students and Balinese parents living in Kabupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
22

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 3 publications
(3 reference statements)
2
11
0
22
Order By: Relevance
“…The adaptation of students supports the assertion that self-regulated learning is one of the key predictors of students' success in learning (Fasikhah & Fatimah, 2013;Kristiyani, 2016;Latipah, 2010;Sutikno, 2016), particularly in online learning that demands students' autonomy (Barnard et al, 2009). Self-regulated learning allows students to identify their direction for learning, understand their talents and interests through the learning materials, make the learning more interesting, challenging, and fun, and avoid uncertainty, confusion, and disappointment (Latipah, 2010;Nadhif & Rohmatika, 2020).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The adaptation of students supports the assertion that self-regulated learning is one of the key predictors of students' success in learning (Fasikhah & Fatimah, 2013;Kristiyani, 2016;Latipah, 2010;Sutikno, 2016), particularly in online learning that demands students' autonomy (Barnard et al, 2009). Self-regulated learning allows students to identify their direction for learning, understand their talents and interests through the learning materials, make the learning more interesting, challenging, and fun, and avoid uncertainty, confusion, and disappointment (Latipah, 2010;Nadhif & Rohmatika, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…In addition to these external factors, internal factors could trigger stress in learning, including self-efficacy, hardiness, optimism, achievement motivation, procrastination, and personality types (Sutjiato et al, 2015;Yusuf & Yusuf, 2020). Several studies suggested that students' success in the education process is determined, such as self-regulated learning (Fasikhah & Fatimah, 2013;Kristiyani, 2016;Latipah, 2010;Sutikno, 2016). Self-regulated learning is the main determining factor for success in online learning, wherein independence is the main trait demanded by online learning (Barnard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Manfaat kedua menurut Kristiyani, T (2020), yaitu penelitian ini dapat memberikan pemahaman tentang faktor-faktor yang mempengaruhi perkembangan metacognitive positif pada anak-anak SD. Informasi ini dapat digunakan untuk mengidentifikasi faktor-faktor yang menghambat atau mendorong perkembangan metacognitive positif dan membantu dalam merancang intervensi yang tepat.…”
Section: Pedagogi: Jurnal Ilmu Pendidikanunclassified
“…Penelitian ini menunjukkan bahwa minat belajar peserta didik tidak hanya dipengaruhi oleh komunikasi guru, tetapi juga oleh faktor-faktor lain. Teori belajar menyatakan bahwa minat belajar dipengaruhi oleh beberapa faktor, di antaranya motivasi internal, persepsi atas kemampuan diri, situasi sosial dan lingkungan, dan komunikasi dari guru [8]. Ketika peserta didik beranjak ke tingkatan yang lebih tinggi, mereka mulai mengalami perubahan dalam hal motivasi dan persepsi atas kemampuan diri [9].…”
Section: Pembahasanunclassified